2021
DOI: 10.1088/1361-6560/abeba9
|View full text |Cite
|
Sign up to set email alerts
|

An automated optimization strategy to design collimator geometry for small field radiation therapy systems

Abstract: Purpose. To develop an automated optimization strategy to facilitate collimator design for small-field radiotherapy systems. Methods and Materials. We developed an objective function that links the dose profile characteristics (FWHM, penumbra, and central dose rate) and the treatment head geometric parameters (collimator thickness/radii, source-to-distal-collimator distance (SDC)) for small-field radiotherapy systems. We performed optimization using a downhill simplex algorithm. We applied this optimization st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous work on single channel collimator optimization utilized the Nelder-Mead downhill simplex algorithm. 23 Compared with Bayesian optimization, the Nelder-Mead approach is less robust to noise and more likely to become stuck in local minima. Depending on the complexity of the objective function, the latter point may or may not be problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on single channel collimator optimization utilized the Nelder-Mead downhill simplex algorithm. 23 Compared with Bayesian optimization, the Nelder-Mead approach is less robust to noise and more likely to become stuck in local minima. Depending on the complexity of the objective function, the latter point may or may not be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first work we are aware of to utilize Bayesian optimization in conjunction with Monte Carlo particle transport. Previous work on single channel collimator optimization utilized the Nelder–Mead downhill simplex algorithm 23 . Compared with Bayesian optimization, the Nelder–Mead approach is less robust to noise and more likely to become stuck in local minima.…”
Section: Discussionmentioning
confidence: 99%
“…Van Herk et al (2000) noted that a Gaussian distribution represents an idealised dose distribution and suggested that SRT likely offers the closest approximation to this ideal, a hypothesis supported by this study. Further backing this concept is the observation by Wang et al (2021) that CK transverse dose profiles for small fields are well approximated by a Gaussian distribution.…”
Section: Uncertainty Versus Idl Percentage Prescriptionmentioning
confidence: 99%
“…A more efficient approach is the use of formal mathematical optimization algorithms to efficiently find an optimal set of parameters according to a user-defined objective function. There are some examples in the literature of this approach: Wang et al implemented the Nelder-Mead method in conjunction with MCNP and to perform single channel collimator design, 4 while Whelan et al used Bayesian Optimization in conjunction with Topas to optimize a novel collimator array. 5 However, at present there is no simple and general-purpose method to incorporate formal optimization routines into Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…There are some examples in the literature of this approach: Wang et al. implemented the Nelder‐Mead method in conjunction with MCNP and to perform single channel collimator design, 4 while Whelan et al. used Bayesian Optimization in conjunction with Topas to optimize a novel collimator array 5 .…”
Section: Introductionmentioning
confidence: 99%